2017
DOI: 10.17523/bia.v74n2p79
|View full text |Cite
|
Sign up to set email alerts
|

Farinha do subproduto de feijão Phaseolus vulgaris em dietas para juvenis de tilápia do Nilo

Abstract: RESUMO: A procura por fontes proteicas alternativas em dietas para peixes é necessária, pois alguns ingredientes proteicos tradicionais apresentam grande variação no preço e disponibilidade. Um experimento de 45 dias foi conduzido em um sistema de recirculação de água com juvenis de tilápia do Nilo (peso inicial de 16,2 ± 0,1 g) para avaliar os efeitos da inclusão de farinha do subproduto de feijão Phaseolus vulgaris sobre os índices produtivos e composição corporal. Três dietas isonitrogenadas (35% de proteín… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…It has been found that even certain levels of inclusion of alternative feeds provide better fish performance indices. In red tilapia (Oreochromis mossambicus X Oreochromis niloticus) up to 30% of sorghum starch can be included in the diets without compromising performance (Abdel and Atallah, 2016), according to Azevedo et al (2017), the inclusion of up to 6.2% of flour of the bean byproduct as a substitute of soybean meal does not diminish the performance of tilapia. Other studies also did not record a reduction in the performance of Nile tilapia with the inclusion of other legumes as an alternative source in the diets.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that even certain levels of inclusion of alternative feeds provide better fish performance indices. In red tilapia (Oreochromis mossambicus X Oreochromis niloticus) up to 30% of sorghum starch can be included in the diets without compromising performance (Abdel and Atallah, 2016), according to Azevedo et al (2017), the inclusion of up to 6.2% of flour of the bean byproduct as a substitute of soybean meal does not diminish the performance of tilapia. Other studies also did not record a reduction in the performance of Nile tilapia with the inclusion of other legumes as an alternative source in the diets.…”
Section: Discussionmentioning
confidence: 99%
“…Outra variável que não apresentou efeito significativo, foi à taxa de eficiência proteica, na qual representa a capacidade do animal em transformar a proteína em massa corporal. Os valores registrados (2,62% a 2,96%) foram superiores aos dados encontrados na literatura para diferentes espécies de peixes que receberam ingredientes proteicos de origem vegetal, (JAYANT et al 2021) obtiveram 1,05 a 1,24% para Labeo rohita recebendo torta de mamona; (AGBOOLA et al 2019) 0,008 a 0,020% para bagre africano com farelo de mamona; (ALEGBELEYE et al 2011) 1,37 a 2,29% para hibrido de Clarias gariepinus X Heterobranchus bidorsalis com farelo de mamona; (AZEVEDO et al 2017) 1,5 a 2,2% para tilápia do Nilo com a farinha do subproduto de feijão Phaseolus vulgaris e (SANTOS et al 2015b) 1,26 a 1,46% para tilápia do Nilo com feno desidratado da folha de mandioca.…”
Section: Variáveis Analisadasunclassified
“…Studies with alternative sources of protein for tilapia production are abundant; however, there are few previous studies on the use of Phaseolus vulgaris. Studies showing the inclusion of up to 6.2% of bean by-product flour for up to 45 days did not affect the performance and body composition of juveniles of Nile tilapia, and it was possible to increase bean residues in the diet (Azevedo et al, 2017).…”
Section: Alternative For Crop Residuesmentioning
confidence: 99%